Cardiovascular diseases ("Internal Medicine". Modul 2). Topics for self-education of students. Part 2 - Berezin, O. E.; Vizir, V. A.; Demidenko, O. V.; Березін, Олександр Євгенійович; Візір, Вадим Анатолійович; Деміденко, Олександр Вікторович (Запорізький державний медичний університет, 2019)
The executive task force is provided for students of 5 th courses of medical institutions of higher education for self-education to study of some topics in the fields of cardiovascular diseases incorporated into the discipline «Internal Medicine». There is the information about the most important topics regarding diagnosis of cardiac diseases.
Захворювання серцево-судинної системи. Питання для самостійної роботи студентів ("Внутрішня медицина". Модуль 2). Ч. 2